2017
DOI: 10.1111/rda.12905
|View full text |Cite
|
Sign up to set email alerts
|

Short communication: Progressive motility of frozen–thawed canine semen is highest five minutes after thawing

Abstract: Progressive motility is usually estimated by visual inspection using a light contrast microscope at X 100 immediately after semen collection or immediately after thawing frozen semen. Standard operating procedures have never been established for this test. The objective of this experiment was to examine time-dependent changes of motility after thawing cryopreserved canine semen. Semen of 35 dogs was collected, and volume, concentration, progressive motility, morphology, membrane integrity and HOS test were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…The present study results are in corroboration with the kinetic parameters reported for jack semen previously (Prashant et al 2019). A significant decrease in total and progressive motility was recorded in all jack stallions, supporting the general agreement that the semen of the donkey was less efficiently frozen and freezing process can contribute to a decline in sperm motility, loss of membrane integrity and acrosome structure and DNA integrity (Karger et al 2017).…”
Section: Resultssupporting
confidence: 91%
“…The present study results are in corroboration with the kinetic parameters reported for jack semen previously (Prashant et al 2019). A significant decrease in total and progressive motility was recorded in all jack stallions, supporting the general agreement that the semen of the donkey was less efficiently frozen and freezing process can contribute to a decline in sperm motility, loss of membrane integrity and acrosome structure and DNA integrity (Karger et al 2017).…”
Section: Resultssupporting
confidence: 91%
“…Sperm DNA damage, loss of membrane integrity, and changes to the acrosome's structure can all be brought on by cryopreservation (Karger et al, 2017;Kim et al, 2010) The aforementioned dangers call for novel approaches to improve canine spermatozoa post-thaw parameters, maximize oocyte fertilization, and boost contraceptive rates.…”
Section: Introductionmentioning
confidence: 99%